International Labour Law in the context of global integration - Lê Văn Bính (Tạp chí Nghiên cứu Khoa học Công đoàn, 2022)
The roles and importance of International labour law, in terms of regional and global integration, have already been verified. To adjust the relations regarding labor and employment in either directly or indirectly ways, these legal norms own specific characteristics and have always been flexible in content, form, as well as in procedural implementation. Researching international labour law is essential not only for people who study laws, but also for students, faculty, employers and employees.